Optimizing Anesthesia for a Pediatric Patient with Cyanotic Heart Disease: Pulmonary Atresia with MAPCAs - Putra, Kadek Agus Heryana; Kurniyanta, I Putu; Subagiartha, I Made; Akbar, Lalu Reza Aldira (Syntax Corporation, 2025)
Pulmonary atresia with major aortopulmonary collateral arteries (MAPCAs) is a rare and complex congenital heart anomaly marked by the absence of a direct connection between the right ventricle and the pulmonary arteries. The pulmonary blood supply originates via collateral arteries that arise from the aorta. Pulmonary atresia with major aortopulmonary collateral arteries (MAPCAs) poses considerable difficulties in perioperative management, especially during general anesthesia for dental procedures in pediatric patients. This case report details the anesthetic management of a 5-year-old male with pulmonary atresia and MAPCAs undergoing dental extractions under general anesthesia. The anesthetic plan prioritized maintaining systemic blood pressure to ensure pulmonary perfusion, avoiding increases in pulmonary vascular resistance, and preventing myocardial depression. Anesthesia was induced with ketamine and fentanyl, while maintenance was achieved using sevoflurane and dexmedetomidine, with pressure-controlled ventilation to optimize hemodynamics. Postoperative recovery was uneventful, with the patient monitored in the pediatric intensive care unit. The management of patients with pulmonary atresia and MAPCAs requires careful planning and a multidisciplinary approach. A tailored anesthetic strategy emphasizing hemodynamic stability and oxygenation is critical. This report underscores the importance of understanding the pathophysiology of MAPCAs to optimize perioperative outcomes.